Comparison of Pharmacokinetic Characteristics of Bilosomal Dispersion Versus Pure Solution of Oral Ropinirole Hydrochloride in Rats - Ali, Samer K.; J. Al-Akkam, Entidhar (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Ropinirole hydrochloride is a non-ergoline antiparkinson drug. It is a highly hydrophilic drug and classified as class III according to Biopharmaceutical Classification System with low absolute oral bioavailability of approximately 50% upon oral administration due to significant hepatic first-pass metabolism. Objective: to compare the pharmacokinetic parameters of Ropinirole when administered orally in the form of an Ropinirole bilosomal dispersion in contrast to an oral Ropinirole solution. Methods: This study involved the use of twelve male Wistar rats, with an average weight of 220±11 g, and these rats were divided into two groups, comprising six rats each. A 1.1 mg/kg doses of pure Ropinirole and Ropinirole bilosomes were administered orally through gavage after reconstituting in distilled water. Ropinirole was quantified in the rat’s plasma using HPLC, subsequently establishing a spiked calibration curve with plasma samples and utilizing paracetamol as an internal standard. The statistics included mean values (± SD; n = 6) for pharmacokinetic parameters, with statistical significance assessed using a student’s t-test. Results: For the oral bilosomes, the values were 9.4±0.11 μg /ml for Cmax, 3±0.00 h for Tmax, and 55.56±2.12 μg h/ml for AUC0-24. In contrast, for the oral solution, the corresponding values were 7.2±0.14 μg/ml for Cmax, 1.5±0.00 h for Tmax, and 23.70±2.23 μg h/ml for AUC0-24. These parameters were significantly higher (P<0.05) as compared with a pure drug solution. The comparative bioavailability of Ropinirole (AUC0-24 oral solution / AUC0-24 oral bilosomes ) is equal to 42.66%, which indicates the bioavailability of the oral RH solution was less than that of RH bilosomal dispersion. Conclusions: The use of nanovesicular carriers (bilosomes) shows significant potential as an effective delivery system for improving the oral bioavailability of ropinirole hydrochloride.